Multiresolution Reflectance Filtering - Tan, Ping; Lin, Steve; Quan, Long; Guo, Baining; Shum, Harry (EGSR '05 Proceedings of the Sixteenth Eurographics conference on Rendering Techniques, 2005)
Physically-based reflectance models typically represent light scattering as a function of surface geometry at the pixel level. With changes in viewing resolution, the geometry imaged within a pixel can undergo significant variations that result in changing reflectance characteristics. To address these transformations, we present a multiresolution reflectance framework based on microfacet normal distributions within a pixel over different scales. Since these distributions must be efficiently determined with respect to resolution, they are recorded at multiple resolution levels in mipmaps. The main contribution of this work is a real-time mipmap filtering technique for these distribution-based parameters that not only provides smooth reflectance transitions in scale, but also minimizes aliasing. With this multiresolution reflectance technique, our system can rapidly and accurately incorporate fine reflectance detail that is customarily disregarded in multiresolution rendering methods.